KAJIAN PERSEPSI PETANI SAYURAN DALAM PENGGUNAAN PUPUK ORGANIK PADA LAHAN GAMBUT DI KELURAHAN KALAMPANGAN, KOTA PALANGKA RAYA KALIMANTAN TENGAH: Revi Sunaryati - Administrator Journal (Agrienvi: Jurnal Ilmu Pertanian, 2019)
ABSTRACTThe purpose of this study was to determine farmers’ perception of using organic fertilizer on peat lands.The study was conducted in the Village of Kalampangan, Palangkaraya City. Data were obtained from 30 samplefarmers using questionnaires. Data were analyzed using descriptive and nonparametric statistics with spearmancorrelation technique. The results of research showed that farmer perception about organic fertilizer using at peatland is in moderate category. The characteristics of organic fertilizer innovation that are relative advantages,compatibility, complexity, probability and observability are positively related to farmers' perceptions of using organicfertilizers.Keywords: perception, organicfertilizer, vegetables, peatland